(untitled) (Journal of Telenursing (JOTING), 2025)
This study aimed to determine the relationship between self-efficacy and spiritual support and self-care behavior in stroke patients. This study used a correlational method with a cross-sectional approach. The results showed a significant relationship between self-efficacy and self-care behavior (p-value = 0.002) and spiritual support and self-care behavior (p-value = 0.001) in stroke patients. Increasing these two factors can increase independence, accelerate recovery, and reduce the risk of complications in stroke patients. Conclusion: There is a significant relationship between self-efficacy and self-care behavior, and self-spiritual support and self-care behavior. Keywords: Self-Care Behavior, Self-Efficacy, Spiritual Support, Stroke